2018
DOI: 10.1177/1120700018781807
|View full text |Cite
|
Sign up to set email alerts
|

Subchondral drilling for chondral flaps reduces the risk of total hip arthroplasty in femoroacetabular impingement surgery at minimum five years follow-up

Abstract: Subchondral drilling under acetabular chondral flaps during surgical treatment of FAI is an effective procedure to reduce the rate of conversion to THA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…The current study adds to the growing body of literature regarding treatment strategies for full-thickness chondral flaps. Haefeli et al 16 found that subchondral drilling under the chondral flap decreased the rate of conversion to THA when compared with simple debridement of the chondral flap. Similarly, Hevesi et al 19 compared microfracture and debridement and reported mHHS, HOS-Sport, and VAS improvements that were similar to those of the microfracture cohort in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The current study adds to the growing body of literature regarding treatment strategies for full-thickness chondral flaps. Haefeli et al 16 found that subchondral drilling under the chondral flap decreased the rate of conversion to THA when compared with simple debridement of the chondral flap. Similarly, Hevesi et al 19 compared microfracture and debridement and reported mHHS, HOS-Sport, and VAS improvements that were similar to those of the microfracture cohort in our study.…”
Section: Discussionmentioning
confidence: 99%
“…21 Size of the cartilage flaps and distribution of cartilage lesions was comparable between the 2 groups and was calculated according to a previously described method ( Table 1 ). 13 At the time of surgery, there was no evidence defining the optimal treatment of acetabular cartilage flaps. Institutional standard treatment at that time was either minimal debridement of the cartilage flap and additional subchondral drilling of the delaminated area (study group) or retaining the cartilage flap with minimal debridement and no further treatment (control group).…”
Section: Methodsmentioning
confidence: 99%
“…Despite that, the clinical scores and the progression of osteoarthritis on conventional radiographs in the remaining patients with a preserved hip did not differ. 13 There are however obvious limitations of conventional radiography in detecting focal changes of cartilage quality. Magnetic resonance imaging (MRI) is more sensitive in detecting subtle morphologic patterns of early joint degeneration secondary to FAI using semiquantitative scores.…”
Section: Introductionmentioning
confidence: 99%
“…23 In 2 hips micro fracturing of the acetabular bone with suturing of the labrum was performed. 25 Our postoperative protocol included the use of a continuous passive motion device to prevent capsular adhesions during hospital stay. After surgery, patients were mobilised with the use of crutches and partial weightbearing of 15 kg for at least 8 weeks.…”
Section: Methodsmentioning
confidence: 99%